Hydrogen Sulfide Attenuated Angiotensin II-Induced Sympathetic Excitation in Offspring of Renovascular Hypertensive Rats - Feng, Xiaohong; Guo, Qi; Xue, Hongmei; Duan, Xiaocui; Jin, Sheng; Wu, Yuming (Frontiers in Pharmacology, 2020)
Objective: Numerous findings have demonstrated a strong association between parental health during pregnancy and cardiovascular disease in adult offspring. This study investigated whether sensitivity to angiotensin II (AngⅡ) is enhanced in offspring of renovascular hypertensive animals and whether hydrogen sulfide (H2S) can attenuate the increased response to AngⅡ in offspring. Method: The systolic blood pressure (SBP) was measured by non-invasive tail-cuff plethysmograpy every two weeks in all offspring from 8 to 16 weeks. After intracerebroventricular microinjection of AngⅡin the offspring, blood pressure, heart rate and renal sympathetic nerve activity were recorded to test the response to Ang II in the offspring. Western blot analysis was used to examine the protein expression of AT1R, AT1R-associated protein (ATRAP), Nox2, p67phox, and nitrotyrosine in the nucleus tractus solitarii (NTS). Results: The SBP in the offspring of hypertensive rats were significantly higher than that in control group, and the above effects were significantly improved by prenatal or postnatal administration of H2S. Intralateroventricular microinjection of AngⅡinduced greater sympathetic responses in offspring of hypertensive rats than control group. The expression of AT1R and oxidative stress-related protein was increased, whereas that of ATRAP was decreased in the NTS in offspring of hypertensive rats. Exogenous administration of H2S prenatally or postnatally improved the above effects. Conclusion: Prenatal or postnatal administration of H2S attenuated AngII-induced sympathetic excitation in offspring of hypertensive rats, which may occur by modulating the balance between AT1R and ATRAP and downregulating oxidative stress-related protein expression in the NTS.